LDC7559 inhibits microglial activation and GSDMD-dependent pyroptosis after subarachnoid hemorrhage - Cai, Wenhua; Wu, Zhe; Lai, Jinqing; Yao, Jieran; Zeng, Yile; Fang, Zhongning; Lin, Weibin; Chen, Junyan; Xu, Chaoyang; Chen, Xiangrong (Frontiers in Immunology, 2023)
Mounting evidence indicates that microglia activation and neuronal pyroptosis play important roles in brain function recovery after subarachnoid hemorrhage (SAH). LDC7559 is a newly discovered gasdermin D (GSDMD) inhibitor. Previous studies have demonstrated that LDC7559 could inhibit microglia proliferation and pyroptosis. However, the beneficial effects of LDC7559 on SAH remain obscure. Based on this background, we investigated the potential role and the mechanism of LDC7559 on SAH-induced brain damage both in vivo and in vitro. The findings revealed that neuroinflammation and pyroptosis were evidently increased after SAH, which could be markedly suppressed by LDC7559 both in vivo and in vitro. Meanwhile, LDC7559 treatment reduced neuronal apoptosis and improved behavior function. Mechanistically, LDC7559 decreased the levels of GSDMD and cleaved GSDMD after SAH. In contrast, nod-like receptor pyrin domain-containing 3 (NLRP3) activation by nigericin increased GSDMD-mediated pyroptosis and abated the beneficial effects of LDC7559 on SAH-induced brain damage. However, LDC7559 treatment did not significantly affected the expression of NLRP3 after SAH. Taken together, LDC7559 might suppress neuronal pyroptosis and microglia activation after SAH by inhibiting GSDMD, thereby promoting brain functional recovery.